L’esprit de Dieu et l’Esprit Saint dans les Questions sur l’Ancien et le Nouveau Testament de l’Ambrosiaster - Bussières, Marie-Pierre (Revue d'études augustiniennes et patristiques, 2010)
Among the quaestiones of Ambrosiaster that have undergone rewriting, one encounters some notable texts where the spirit of God is not always identified as the Holy Spirit. From one version to the other, moreoever, the author introduces the notion of consubstantiality in order to explain the nature of the Holy Spirit, which is uncommon in the Latin West at the end of the 4th century. We attempt to analyze what is behind these modifications, chiefy in light of contemporary exegeses of Gen 1:2, and to propose a date for the different versions of Ambrosiaster’s quaestiones on the matter.